BITCOIN PRICE PREDICTION USING LONG SHORT TERM MEMORY ALGORITHM - Fauzi, Rifqi Arul; Rohana, Tatang; Nurlaelasari, Euis; Wahiddin, Deden (Information Technology and Science (ITScience), 2025)
Bitcoin a digital asset with the largest market capitalization in the world and shows high price volatility, attracting the interest of researchers to make accurate price predictions. The research aims to build a Bitcoin price prediction model use Long Short-Term Memory (LSTM) algorithm by utilizing closing price data and technical indicator variables, Moving Average (MA) and Exponential Moving Average (EMA). Dataset obtained from Yahoo Finance with a time range of January 1, 2015 to January 1, 2024 as much as 3287 data. The LSTM model is designed in multivariate form with an input sequence of 30 with several test scenarios at the epoch number 50, 100 and 200. Model evaluation is based on 4 metrics, namely Root Mean Squared Error (RMSE), Mean Squared Error (MSE), Mean Absolute Error (MAE), and Mean Abso-lute Percentage Error (MAPE). Model evaluation results show that the model is capable of providing a good prediction value with an MSE value of 0.0001, RMSE of 0.0117, MAE of 0.0081, and MAPE of 2.21% at epoch 200. The use of technical indicators proved to be helpful in improving the performance of the model compared to using only closing price data.